Digital Marketing Literacy to Sustain MSME Businesses in Southwest Papua - Satria Lintang Rachmadana; Pahmi Pahmi; Sabaria Sabaria; Hamsiah Hamsiah; Inri De Fretes (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
This research aims to determine the extent to which Micro, Small and Medium Enterprises (MSMEs) in Southwest Papua understand digital marketing to sustain their business. This study focuses on factors influencing digital literacy, business resilience, and entrepreneurial orientation in MSMEs in the region. A survey method was employed by collecting data from 80 randomly selected MSME samples in the City and Regency of Sorong of Southwest Papua Province. A quantitative approach using structural partial least squares equation modeling (PLS-SEM) was utilized to predict and confirm the hypotheses. Findings unveiled that digital marketing literacy could explain entrepreneurial orientation and business resilience. This study is the beginning of research on the digital economy in the Papua region. The findings of this study successfully answered four hypotheses: (1) There was an influence between digital marketing literacy and entrepreneurial orientation, with a p-value of 0.001 and a regression path of 0.772; (2) There was an influence between digital marketing literacy and business resilience, with a p-value of 0.042 and a regression path value of 0.185. These results revealed that MSME players have been familiar with digital literacy despite residing in Papua.